Bacteroides uniformis Ameliorates Carbohydrate and Lipid Metabolism Disorders in Diabetic Mice by Regulating Bile Acid Metabolism via the Gut-Liver Axis - Xue-Xue Zhu; Chen-Yang Zhao; Xin-Yu Meng; Xiao-Yi Yu; Lin-Chun Ma; Tian-Xiao Chen; Chang Chang; Xin-Yu Chen; Yuan Zhang; Bao Hou; Wei-Wei Cai; Bin Du; et al. (MDPI AG, 2024)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic syndrome characterized by chronic inflammation, insulin resistance, and islet cell damage. The prevention of T2DM and its associated complications is an urgent public health issue that affects hundreds of millions of people globally. Numerous studies suggest that disturbances in gut metabolites are important driving forces for the pathogenesis of diabetes. However, the functions and mechanisms of action of most commensal bacteria in T2DM remain largely unknown. Methods: The quantification of bile acids (BAs) in fecal samples was performed using ultra-performance liquid chromatography-tandem mass spectrometer (UPLC-MS/MS). The anti-diabetic effects of Bacteroides uniformis (B. uniformis) and its metabolites cholic acid (CA) and chenodeoxycholic acid (CDCA) were assessed in T2DM mice induced by streptozocin (STZ) plus high-fat diet (HFD). Results: We found that the abundance of B. uniformis in the feces and the contents of CA and CDCA were significantly downregulated in T2DM mice. B. uniformis was diminished in diabetic individuals and this bacterium was sufficient to promote the production of BAs. Colonization of B. uniformis and intragastric gavage of CA and CDCA effectively improved the disorder of glucose and lipid metabolism in T2DM mice by inhibiting gluconeogenesis and lipolysis in the liver. CA and CDCA improved hepatic glucose and lipid metabolism by acting on the Takeda G protein-coupled receptor 5 (TGR5)/adenosine monophosphate-activated protein kinase (AMPK) signaling pathway since knockdown of TGR5 minimized the benefit of CA and CDCA. Furthermore, we screened a natural product-vaccarin (VAC)-that exhibited anti-diabetic effects by promoting the growth of B. uniformis in vitro and in vivo. Gut microbiota pre-depletion abolished the favorable effects of VAC in diabetic mice. Conclusions: These data suggest that supplementation of B. uniformis may be a promising avenue to ameliorate T2DM by linking the gut and liver.